Fresno County Counsel Baby Shower for Leticia Aleman - Watkins, Howard::::::::: (1987)
Thomas Riggs, Barbara Christiansen, Helen Apodaca, Mary Herrick, Catherine Dominguez, Debbie Lucas, Phillip Jay, Leticia Aleman, John Duffy and Vickie Stoutingberg Office library at Suite 121 Plaza Level Golden State Plaza